Glutamatergic lateral hypothalamus promotes defensive behaviors. (1st November 2020) - Chen, Li; Cai, Ping; Wang, Ren-Fei; Lu, Yi-Ping; Chen, Hui-Yun; Guo, Yu-Rou; Huang, Sheng-Nan; Hu, Li-Huan; Chen, Jian; Zheng, Ze-Hong; He, Peng; Zhang, Bing-Feng; et al.
Abstract: The glutamatergic lateral hypothalamus (LH) has been implicated in a variety of behaviors, such as evasion and feeding, while its role in defensive behaviors and relevant neurocircuits remains unclear. Here, we demonstrated that the glutamatergic LH is a critical structure regulating defensive behaviors. Trimethylthiazole (TMT), the odor of mice predator, significantly increased c-Fos expression in the LH. Using fiber photometry technology, we found that TMT exposure increased the activity of LH glutamatergic neurons. Selective activation of LH glutamatergic neurons with optogenetics and chemogenetics promoted a series of defense-related behaviors, including fleeing, avoidance, and hiding, while selective inhibition of LH glutamatergic neurons suppressed the avoidance provoked by TMT. Activation of both the glutamatergic LH terminals in the hypothalamic paraventricular nucleus (PVN) and the glutamatergic projection from the basolateral amygdala (BLA) to the LH elicited defensive behaviors. Finally, by combining the viral-mediated retrograde tracing with anterograde activation, we found that PVN-projecting glutamatergic neurons in the LH were activated by BLA glutamatergic inputs. Taken together, our results illustrate that the glutamatergic LH is a pivotal relay of defensive behaviors and possibly promotes these behaviors through the BLA→LH→PVN pathway. Highlights: Trimethylthiazole (TMT), the odor of mouse predator, increases the activity of LH glutamatergic neurons in mice. Activation of LH glutamatergic neurons promotes a series of defensive behaviors, including fleeing, avoidance and hiding; while inhibition of these neurons suppresses the TMT-induced avoidance. Optogenetic activation of LH glutamatergic terminals in the hypothalamic paraventricular nucleus (PVN) induces defensive behaviors. Retrograde activation of the glutamatergic projection from the basolateral amygdala (BLA) to the LH induces defensive behaviors. The PVN-projecting glutamatergic neurons in the LH are activated by BLA glutamatergic inputs.